MODEL PENYELESAIAN PELANGGARAN PENANGKAPAN IKAN MENURUT HUKUM ADAT MASYARAKAT MANTULIK - HALIMAH NOVITA SARI; Erdianto Erdianto; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The culture of modern society is now intended by social deviations in thewater area, that is, people catch fish by bombing usin0scng dynamite, electrocution,and using cyanide chemicals used in the sea. Meanwhile, in the river, fish are caught bytuba / mutas fish and catching fish by electrocution. The above methods are contrary totraditional wisdom in managing, utilizing the environment. Today's society has amindset that only attaches importance to the current life. But it does not attachimportance to the future lives of posterity, so in taking advantage of this nature they arearbitrarily destructive. So that the original face of nature and culture loses itsidentity by human actions. Something similar happened in Mentulik Village,Kampar Kiri District, Kampar Regency. Where Mentulik Village is one of thevillages flowing by the left kampar river.The objectives in this thesis research are: First, How the settlement modelcarried out by indigenous peoples determines fishing violations, Second, What are theobstacles faced in carrying out fishing violations. This type of research is classifiedas a type of Sociological Juridical research. This research was conducted inMentulik Village, Kampar Hilir City District, Kampar Regency, while thepopulation and samples in this study were all parties related to the problem studied.The data sources used are primary data, secondary data and tertiary data. Datacollection techniques in this study are interviews, observations and literature studies.Based on the results of research, the resolution of fishing violations accordingto customary law of the mentulik community is more effective because the sanctionsgiven are adjusted to the socioeconomic conditions of the perpetrators and consideringthe problem of overcapacity that occurs in Indonesia. Customary law also emphasizesthe value of kinship where big problems are minimized and small problems areeliminated, customary law also ensures that problems that have been resolved in acustomary manner must be completely resolved and no longer in question in thefuture.Keywords: Settlement- Fishing- Sanctions- Customary Law.